THE LEGAL POLICY OF IMPLEMENTING AUTOMATIC EXCHANGE OF INFORMATION (AEOI) IN INDONESIA: WHAT AND HOW? - Sediati, Diah Sulistyani Ratna; Arifin, Zaenal (Faculty of Law, Universitas Pekalongan, 2024)
The Automatic Exchange of Information (AEOI) is a scheme for the automatic exchange of financial information between countries to combat tax evasion and money laundering. Indonesia has established AEOI through Law Number 9 of 2017 and Minister of Finance Regulation Number 60/PMK.03/2017, taking into account various economic, social, and political interests in its legal political process. The purpose of this research is to analyze the legal politics behind the establishment of the Automatic Exchange of Information (AEOI) in Indonesia and to formulate effective and efficient implementation strategies in the government's efforts to combat tax evasion and money laundering through the scheme of automatic exchange of financial information between countries. This research uses normative legal research methods, focusing on examining and analyzing the applicable legal norms. The sources of legal materials used in this research consist of primary, secondary, and tertiary legal materials, with data collection techniques in the form of literature studies and data analysis conducted qualitatively. The research results reveal that the legal politics behind the establishment of the Automatic Exchange of Information (AEOI) in Indonesia are based on efforts to align with international standards in combating cross-border tax evasion and money laundering, enhancing fiscal transparency, strengthening law enforcement in the field of taxation, and increasing state revenue from the tax sector. The implementation of AEOI can be carried out effectively and efficiently by ensuring a strong legal framework, developing reliable information technology infrastructure, enhancing human resource capacity, building cooperation and coordination with financial service institutions and partner countries, conducting monitoring and evaluation, and raising public awareness and education about the importance of AEOI in combating cross-border tax evasion and money laundering.